INTERNAL QUALITY ASSURANCE SYSTEM IN ONLINE LEARNING AT ELEMENTARY SCHOOL - Dwi Erawati Susanto; Fitri Nur Mahmudah (Jurnal Penjaminan Mutu, 2022)
The quality of education is closely related to whether or not the national education objectives are achieved. Therefore, education is said to be good if it meets the national standards of education. The fulfillment of national standards of education, the minimum standard of education, is the initial requirement for improving the quality of education. Many schools do not meet national standards of education, including standards of skills and competencies, because teachers and educational personnel do not have adequate facilities and infrastructure. This article aims to explain the evaluation of quality assurance of education in improving the quality of education in elementary schools. This study uses qualitative methods. Data retrieval is done through interviews and documentation. The interview speaker took the object of the principal and the class teacher in the school. While related documentation taken from photos, evidence of school administration. The results obtained from this study that in the internal quality assurance system in schools have been good in its implementation because all processes have a clear basis and are consulted in the school forum. Several determining factors of success in the implementation of the internal quality assurance system are effective principal leadership, commitment and consistency of stakeholders, accountability, transparency and integrity.